Artificial Intelligence in English Language Learning: A Systematic Review of Applications, Benefits, and Challenges in EFL Classrooms - Muhammad Idul; Mujahidah; Ramdani, Amaliah (Inspiring: English Education Journal, 2026)
The swift progress in Artificial Intelligence (AI) has had a large impact on education, particularly in English as a Foreign Language (EFL) instruction. This study systematically examines how AI technologies are used in English language learning, their benefits, and the difficulties they present. It employed a systematic review approach and followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Thirty studies from 2019 to 2025 were taken from Scopus and Web of Science. The results show that AI conversation programs, automated writing evaluation systems, speech-to-text software, and adaptive learning platforms have been used to support language learning. These technologies provide immediate feedback, personalized learning, and increased opportunities for language use. The studies also indicate improvements in writing accuracy, speaking fluency, vocabulary development, communicative competence, as well as student engagement and motivation. However, several problems were found, including limited technological infrastructure, low teacher digital competence, ethical concerns, and the risk of overdependence on AI. Overall, this research highlights the potential of AI technologies to support language learning and provides useful guidance for teachers, researchers, and policymakers.